Pengaruh Transformasi Digital dan Stres Kerja terhadap Kinerja Karyawan yang Dimediasi oleh Keterlibatan Karyawan pada Sekretariat Daerah Kabupaten Pati - Nurma Isnawati; Jati Waskito (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The changing era of digital transformation requires human resources to have insight and mastery in using technology digitally. The involvement of human resources in digital transformation is very important in an organization, because HR is the driver of all activities to achieve organizational goals and strive for progress in employee performance. The aim of this research is to analyze the influence of digital transformation and work stress on employee performance and employee engagement and to analyze the role of employee engagement as a mediator on the influence of digital transformation and work stress on employee performance. This research uses quantitative research by distributing questionnaires to 104 Pati Regency Regional Secretariat Employees. The results of data processing using SEM PLS 3.0 state that there is a significant positive influence on digital transformation on employee performance and employee engagement, there is a significant negative influence on job stress on employee performance and employee engagement, and employee engagement is proven to mediate the influence of digital transformation and job stress on employee performance.